Flusslandschaften In Mittelalter und Moderne - Hülsen-Esch, Andrea (studia humaniora, 2023)
Rivers have always been a formative component of spaces. They serve as natural borders, mold the character of a landscape, shape how entire regions look, and often mark politically contested border areas. At the same time, river landscapes constitute spaces of contact and exchange, thereby helping spatial cultures and cultural spaces to grow. The aim of this volume is to outline the diversity of river landscapes.